2004
DOI: 10.1017/s0022109000003987
|View full text |Cite
|
Sign up to set email alerts
|

Economic Sources of Gain in Stock Repurchases

Abstract: Previous studies offer a mixed understanding of the economic role of stock repurchases. This paper investigates three key economic motivations-mispricing, disgorging free cash flow, and increasing leverage-by evaluating cross-sectional differences in both the initial market reaction and long-run performance. The initial reaction provides some support for the mispricing story. However, subsequent earnings-related information shocks suggest that the initial market reaction is incomplete and that long-run perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
170
3
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(197 citation statements)
references
References 42 publications
(43 reference statements)
16
170
3
4
Order By: Relevance
“…The results reported in Table 4 (Panel C) show that for the pooled sample the small-firms portfolio consistently outperforms the large-firms portfolio for all holding periods up to 9 months, after which the pattern is reversed and large stocks outperform the small stocks in the longer run. This is also in line with Chan et al (2004) who find that at the time of the announcement smaller firms enjoy a higher market reaction but on the long run (a four year holding period) it is large firms that have a better stock price performance. For the country-specific portfolios, we observe that in France, with the exception of the first month the small-stocks portfolio consistently outperforms the large stocks for all holding periods.…”
Section: Logistic Regressionssupporting
confidence: 90%
See 1 more Smart Citation
“…The results reported in Table 4 (Panel C) show that for the pooled sample the small-firms portfolio consistently outperforms the large-firms portfolio for all holding periods up to 9 months, after which the pattern is reversed and large stocks outperform the small stocks in the longer run. This is also in line with Chan et al (2004) who find that at the time of the announcement smaller firms enjoy a higher market reaction but on the long run (a four year holding period) it is large firms that have a better stock price performance. For the country-specific portfolios, we observe that in France, with the exception of the first month the small-stocks portfolio consistently outperforms the large stocks for all holding periods.…”
Section: Logistic Regressionssupporting
confidence: 90%
“…1995Ikenberry at al. , 2000McNally and Smith 2007) which tend to persist in the long-run, hence offering economic sources of gain to long-term shareholders (Ikenberry and Vermaelen 1996;Chan et al 2004). Since open market share repurchases are not firm commitments, they are essentially options that managers can use when they believe the firm's share price is undervalued.…”
Section: Introductionmentioning
confidence: 99%
“…By using buy-and-hold returns over 4 years, Chan et al (2004) found that high BTM companies have larger returns over their matched sample which is 28.35% compared with 22.92% for low BTM companies. Firms with high BTM, or "value stocks," were also proven by Hackethal and Zdantchouk (2006) to have outperformed the "glamour stocks" or firms with low BTM by 45%.…”
Section: Methodsmentioning
confidence: 99%
“…Market capitalization has been identified as an important factor by local and overseas researchers in determining the share price performance following share buyback programs (Chan et al, 2004;Ikenberry et al, 1995;Vermaelen, 1981;Wong et al, 2011;Zhang, 2005). These studies including Ramakrishnan et al (2007) found that information asymmetry which has caused greater undervaluation and mispricing is larger in small firms due to less public disclosure and focus by the analysts as compared with bigger firms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation